Implementasi Algoritma Alpha-Beta Pruning pada Permainan Bantumi dengan Berbasis Mobile Android - Jati Lestari; Siti Annisa Amalia (Bit (Fakultas Teknologi Informasi Universitas Budi Luhur), 2013)
Bantumi or so-called Mancala or Congklak, is a traditional game which belong to the type of strategy game that is played by two players. Along with the development of technology, particularly in smartphones, then made this Bantumi traditional game to make it more practical to play is by expanding into the Android mobile-based application form. With the help of Artificial Intelligence (AI), the computer will be able to play and think to beat his opponent as well as humans. Alpha-Beta Pruning Algorithm is the best step search algorithm used in this Bantumi application in determining the best move. By using this algorithm, the computer will do a search with the best possible move. The higher the depth of the search, the better the computer will determine the pace of the game so that the computer will be more difficult to defeat. That's needed for a high concentration of the players in the play, in order to train and improve the skills of logic that is in them.Keywords: bantumi, alpha-beta pruning, algorithms, android